Estimating adult HIV prevalence in the UK in 2003: the direct method of estimation. (29th May 2006) - McGarrigle, C A; Cliffe, S; Copas, A J; Mercer, C H; DeAngelis, D; Fenton, K A; Evans, B G; Johnson, A M; Gill, O N
Abstract : Background: Estimates of the total number of prevalent HIV infections attributable to the major routes of infection make an important contribution to public health policy, as they are used for planning services. Methods: In the UK, estimates were derived through the "direct method" which estimated the total number of diagnosed and undiagnosed HIV infections in the population. The direct method has been improved over a number of years since first used in 1994, as further data became available such as the inclusion of newly available behavioural survey data both from the National Survey of Sexual Attitudes and Lifestyles (Natsal 2000) and community surveys of men who have sex with men (MSM). These data were used to re-estimate numbers of people unaware of their infection and provided ethnic breakdowns within behavioural categories. The total population was divided into 10 mutually exclusive behavioural categories relevant to HIV risk in the UK—for example, MSM and injecting drug users. Estimates of the population size within each group were derived from Natsal 2000 and National Statistics mid-year population estimates. The total number of undiagnosed HIV infections was calculated by multiplying the undiagnosed HIV prevalence for each group, derived from the Unlinked Anonymous HIV Prevalence Monitoring Programme surveys (UAPMP), by the population size. These estimates were then added to the prevalent diagnosed HIV infections within each group derived from the national census of diagnosed HIV infections, the Survey of Prevalent HIV Infections Diagnosed (SOPHID). The estimates were then adjusted to include all adults in the UK. Because undiagnosed HIV prevalence estimates were not available for each of the behavioural categories, the UAPMP prevalence estimates were adjusted using available data to provide the best estimates for each group. Results: It is estimated that 53 000 individuals are infected with HIV in the UK in 2003, of whom 27% were unaware of their infection. Of the total of 53 000, an estimated 26 000 were among heterosexually infected and 24 500 among MSM. Conclusion: The direct method uses an explicit framework and data from different components of the HIV surveillance system to estimate HIV prevalence in the UK, allowing for a comprehensive picture of the epidemic.